Language Education from a South American Perspective: What does Latin America have to say? - Barboni, Silvana Julieta (2013)
The focus of this book is on linguistic educational policies in Latin America. As many books do, this one started with conversations round a table of friends on what is academically and politically blooming in this part of the world as a result of complex political, social and educational drives. The recognition that Latin America is with no doubt a virgin land is at the basis of this book. It is a land where several educational policies are being implemented for the first time in history, for different languages and for different purposes - policies which are intended to address the complex linguistic scenario of the region in some way. Unlike other parts of the world, the attempts to bring to the spotlight the relevance of a diversity of languages (languages with different statuses) have been chaotic but they have, somehow, given way to a systematic organizational culture that is reconciling the role of languages in education at different levels -compulsory as well as non compulsory schooling- beyond traditional views of languages and their roles. The distinct feature of this drive is that it is not restricted to curricular innovation. It is suggestive that similar drives are turning up in different countries and that different experiences in different regions bear similar theoretical understandings. Although this might be related to the current internationalization trends around the world, the contributions of this volume opened up a series of interesting questions to us as editors of this book. Is this not perhaps the result of Latin America listening to the needs of its people? What are these drives saying about the local? How do socioeconomic policies play a role in linguistic development? How is Latin America looking at its own diversity and the world? Where are we going? From this perspective, this book is definitely about language education in a specific setting. Each contribution describes problems, challenges, and solutions for specific circumstances - circumstances which have arisen from a specific historical context, and consequently make each case unique.